2010
DOI: 10.1016/j.jjcc.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Relation between prognosis and myocardial perfusion imaging from the difference of end-point criterion for exercise stress testing: A sub-analysis of the J-ACCESS study

Abstract: Exercise SPECT imaging provides the useful prognostic information in patients who do not reach a significant end-point due to the leg fatigue. In such patients, those with normal SSS score and normal resting ESV have also a most favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The results showed that the presence of non-obstructive LAP on MDCT was associated with increased likelihood of ACS during a 3-year follow-up. Theoretically, these non-obstructive plaques are not detectable on other noninvasive modalities, such as exercise electrocardiography, stress single-photon emission computed tomography, or stress echocardiography, each of which is designed to detect myocardial ischemia [26,27]. In this regard, invasive catheter-based techniques (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the presence of non-obstructive LAP on MDCT was associated with increased likelihood of ACS during a 3-year follow-up. Theoretically, these non-obstructive plaques are not detectable on other noninvasive modalities, such as exercise electrocardiography, stress single-photon emission computed tomography, or stress echocardiography, each of which is designed to detect myocardial ischemia [26,27]. In this regard, invasive catheter-based techniques (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…23 Compared to previous studies, our results showed a higher percentage of CD in the normal visual and quantitative perfusion group, and similar survival rates for the first year than reported in other studies. 4,27,28 This is likely due to the particular selection, case-control design with a 1:1 match and long follow-up. Our study differs from the other prognostic studies since it is a retrospective case-control study that was done on a very selected group of CD patients and compared to a clinical matched alive controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some large-scale prognostic studies using myocardial perfusion SPECT were conducted in Japan, and the study reports and the sub-analysis reports have been published one after another [4][5][6][7][8][9]. Nishimura et al have been conducting the multicenter prospective Japanese Assessment of Cardiac Events and Survival Study (J-ACCESS), since 2001 to evaluate the prognostic value of stress myocardial perfusion SPECT in patients with suspected or confirmed ischemic heart diseases.…”
Section: Introductionmentioning
confidence: 99%